SISTEM INFORMASI GEOGRAFIS LETAK LOKASI RUMAH SAKIT DAN APOTEK KOTA BENGKULU BERBASIS ANDROID - Deti Marlena; Hari Aspri yono (UNIVED Press, 2014)
Evolving current technologies such as mobile technology, its One Android smartphone technology, with the advancement of technology information system layout and Apotekpun Hospital location can be searched via the android smartphone. The purpose of this research is aimed to make the mapping location-based services (LBS) android based bengkulu tour. This application can help the City Health Department to find out where the course layout Hospital and Pharmacy Loca-tions that have been established. The application is built Android using Java programming ADT software Bundle in which there is Eclipse as editor java programming language, as a plugin for the Eclipse ADT, and the SDK for Android based application development interests. The end result of this research is a system information application layout and location of the hospital-based pharmacies android. Information Systems and Location of Hospital Pharmacy Location This facilitates the City and the public health department to locate the location of hospitals and pharmacies in the city of Bengkulu.Keywords: Geographic Information Systems, Hospital, Pharmacy, Android